2005
DOI: 10.1017/s1461145705006218
|View full text |Cite
|
Sign up to set email alerts
|

Association between monoamine oxidase gene polymorphisms and smoking behaviour in Chinese males

Abstract: Monoamine oxidase (MAO) is a critical metabolic enzyme of dopamine, which is a key neurotransmitter of the mesolimbic reward pathway in the human brain. Consequently, the gene encoding MAO is an important candidate gene in the genetics of smoking behaviour. We investigated the association between MAOA polymorphisms (a VNTR polymorphism and an EcoRV polymorphism) and smoking status. A community-based cross-sectional study was conducted with 203 current smoking subjects and 168 non-current smoking subjects in Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…106 Another study of Chinese males found those with both the four-repeat allele and 1460C allele were least likely to be current smokers. 107 In adolescents, no associations of the MAO-A VNTR polymorphisms or 1460C4T SNP were found between current, former or never smokers. 82 Catechol-O-methyltransferase is important in the degradation catecholamines, and a functional SNP (1947G4A) corresponding to Val108/158Met has been identified.…”
Section: Mk Ho and Rf Tyndalementioning
confidence: 93%
“…106 Another study of Chinese males found those with both the four-repeat allele and 1460C allele were least likely to be current smokers. 107 In adolescents, no associations of the MAO-A VNTR polymorphisms or 1460C4T SNP were found between current, former or never smokers. 82 Catechol-O-methyltransferase is important in the degradation catecholamines, and a functional SNP (1947G4A) corresponding to Val108/158Met has been identified.…”
Section: Mk Ho and Rf Tyndalementioning
confidence: 93%
“…Ito et al 86 and Jin et al 87 reported that individuals with the 3-repeat allele had a greater risk of smoking, when compared to those with the 4-repeat allele in Asian populations. In contrast, Wiesbeck et al 88 reported an association between the 4-repeat allele and a greater quantity of daily cigarettes in Caucasian men with both alcohol and tobacco dependence.…”
Section: Tobacco Smokingmentioning
confidence: 99%
“…Some studies have shown a positive association between the high-activity alleles and an increased risk of nicotine dependence, 155–157 but other studies have failed to confirm this association. 158,159 These studies have many procedural differences, including the gender, age and other characteristics of the sample population and the definition of dependence, which make direct comparisons difficult.…”
Section: Indirect Influence Of Molecular Variation On Nicotine Dependmentioning
confidence: 99%